2019
DOI: 10.1002/ecs2.2664
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent changes in cichlid dentition linked to climate‐driven lake‐level fluctuations

Abstract: Climate‐induced habitat change has often been invoked as an important driver of speciation and evolutionary radiation in cichlid fishes, yet studies linking morphological change directly to long‐term environmental fluctuations are scarce. Here, we track changes through time in the oral dentition of Oreochromis hunteri, the endemic and only indigenous fish species inhabiting the East African crater Lake Chala (Kenya/Tanzania), in relation to climate‐driven lake‐level fluctuations during the last 25,000 yr. Foss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The closest relationship was with haplochromines from Lake Chala, which the authors interpret as indicative of a former natural connection between the two water bodies. However, subsequent authors have suggested that the haplochromines in Chala are not native (Moser et al 2018;Dieleman et al 2019). We would identify all these as representing the 'sparsidens' lineage of Astatotilapia bloyeti, which is consistent with the illustration of a freshly collected male from Ngare Nanyuki.…”
Section: Discussionsupporting
confidence: 81%
“…The closest relationship was with haplochromines from Lake Chala, which the authors interpret as indicative of a former natural connection between the two water bodies. However, subsequent authors have suggested that the haplochromines in Chala are not native (Moser et al 2018;Dieleman et al 2019). We would identify all these as representing the 'sparsidens' lineage of Astatotilapia bloyeti, which is consistent with the illustration of a freshly collected male from Ngare Nanyuki.…”
Section: Discussionsupporting
confidence: 81%
“…Recovering fish macroremains (e.g. teeth) from sediment cores can help track morphological evolution of ecologically relevant traits [14] and past patterns of fish community composition [15]. Applying these methods within a broader paleolimnological approach could help us understand both microevolutionary dynamics of populations (e.g.…”
Section: Recent Advances In Paleolimnologymentioning
confidence: 99%
“…Often, selective environments are influenced by multiple interacting biotic and abiotic factors and the link between organismal phenotype and fitness is both complex and environmentally contingent [35]. Integrating paleolimnological evidence with geological records of phenotypic variation allows us to examine how changing ecological conditions drive morphological variation in key taxa and test hypotheses about past selective environments [5,14]. The continuous archives of phenotypic data preserved in lake sediments spanning from annual to millennial timescales provide unique and complementary insights into the temporal dynamics of phenotypic evolution.…”
Section: Improving Our Inference About Past Selective Environments An...mentioning
confidence: 99%
See 1 more Smart Citation
“…In many of these study systems, such as Darwin's finches, Heliconius butterflies, Hawaiian silverswords or Anolis lizards, a challenge for palaeogenetics is the scarcity of well-preserved fossil remains. An exception to this general paucity of fossils from geologically young and extant radiations are the cichlid fishes of East Africa, which can leave chronologically highly resolved records of bones, bone fragments, teeth and scales in the sediments of lakes (Ngoepe et al, 2023;Cohen et al, 2016;Dieleman et al, 2015Dieleman et al, , 2019Muschick et al, 2018;Reinthal et al, 2010). Yet, whether such remains contain appreciable amounts of endogenous aDNA is unknown.…”
Section: Introductionmentioning
confidence: 99%